2010
DOI: 10.3164/jcbn.11-006fr
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-derived oxidation: mechanisms of biological damage and its prevention

Abstract: There is considerable interest in the role that mammalian heme peroxidase enzymes, primarily myeloperoxidase, eosinophil peroxidase and lactoperoxidase, may play in a wide range of human pathologies. This has been sparked by rapid developments in our understanding of the basic biochemistry of these enzymes, a greater understanding of the basic chemistry and biochemistry of the oxidants formed by these species, the development of biomarkers that can be used damage induced by these oxidants in vivo, and the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
240
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(253 citation statements)
references
References 229 publications
(271 reference statements)
5
240
0
8
Order By: Relevance
“…In most enzymes, such radical rearrangement is considered to be a protective mechanism. Radicals in proteins can also be very destructive if they form at or migrate to the wrong place [13][14][15][16][17][18][19]. Once generated, the radicals can cause oxidative cleavage along the backbone of the protein [13][14][15][16][17][18][19], which could cause the loss of function of the protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most enzymes, such radical rearrangement is considered to be a protective mechanism. Radicals in proteins can also be very destructive if they form at or migrate to the wrong place [13][14][15][16][17][18][19]. Once generated, the radicals can cause oxidative cleavage along the backbone of the protein [13][14][15][16][17][18][19], which could cause the loss of function of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Radicals in amino acids, peptides, and their derivatives have been examined using various experimental [7,8,21] and computational techniques [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Developments in the understanding of the biochemistry of myeloperoxidase, the oxidants that this enzyme generates, and the use of inhibitors to inhibit such damage have been reviewed recently [35].…”
Section: Resultsmentioning
confidence: 99%
“…21 Targets and actions of the oxidants generated by MPO and mechanisms of its biological damage are reviewed elsewhere. 22 We found that only the effective dose of PRP-1 (4 µg) could decrease the MPO content in the myocardium during IRI in a timedependent manner. Despite the administration of PRP-1, there are plenty of brown granules of oxybenzidine pointing to an unusual activity of MPO and indirectly confirm the infiltration of neutrophils following 2 h reperfusion, whereas they virtually disappear following 24 h reperfusion (Fig.…”
Section: Conditionsmentioning
confidence: 92%